Event-triggered robust formation control of multi quadrotors for transmission line inspection - Tamba, Tua Agustinus; Cinun, Benedictus Christo Geroda; Nazaruddin, Yul Yunazwin; Romdlony, Muhammad Zakiyullah; Hu, Bin (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2024)
This paper proposes an event-triggered formation control scheme to manage the operation of multiple quadrotors in performing the inspection of a power transmission line. In particular, the problem of controlling such multi quadrotors to track the tower and/or cables of the transmission lines is considered. A multi-agent sliding mode control method is used for this purpose and is equipped with both a radial basis function neural network as an estimator of environmental wind disturbances, as well as an event-triggered scheduling scheme for the control execution framework. The proposed multi quadrotors control method is designed by considering the transmission tower/cable as the reference sliding surface. Simulation results are presented to illustrate the effectiveness of the proposed multi quadrotors control scheme when implemented in a case scenario of tracking the commonly-encountered shape of transmission cables. Simulation results are presented and show how the implementation of a position error-based event-triggered control enables all UAVs to track the desired position and maintain a pre-determined formation. In particular, all UAVs can minimize the tracking error within 0.05 m after reaching the desired positions since the control signal is updated if the error reaches such an error bound.